Expression of lncRNAs in glioma: A lighthouse for patients with glioma - Xiaolin Lu; Dongzhi Zhang (Heliyon, 2024)
Glioma is the most common malignant tumour in the central nervous system, accounting for approximately 30 % of the primary tumours of this system. The World Health Organization grades for glioma include: Grade I (pilocytic astrocytoma), Grade II (astrocytoma, oligodastoma, etc.), Grade III (anaplastic astrocytoma, anaplastic oligodastoma, etc.) and Grade IV (glioblastoma). With grade increases, the proliferation, invasion and other malignant biological properties of the glioma are enhanced, and the treatment results are less satisfactory. The overall survival of patients with glioblastoma is less than 15 months. Recent research has focused on the roles of long non-coding RNAs, previously regarded as ''transcriptional noise'', in diseases, leading to a new understanding of these roles. Therefore, we conducted this review to explore the progress of research regarding the expression and mechanism of long non-coding RNAs in glioma.